Co-creation as the Key to a Public, Thriving, Inclusive and Meaningful EU IoT - van Kranenburg, Rob; Stembert, Nathalie; Moreno, M. Victoria; Skarmeta, Antonio F.; López, Carmen; Elicegui, Ignacio; Sánchez, Luis (Ubiquitous Computing and Ambient Intelligence. Personalisation and User Adapted Services, 2014)
Contrary to the general approach of creating Internet of Things (IoT) services from a business perspective, the SOCIOTAL project addresses the design of citizen centered IoT solutions. For this, it is required to create new IoT solutions from the citizens’ point of view and for the immediate benefit of the citizens without necessarily involving city or commercial service providers. A co-creation approach towards definition of user scenarios is adopted by the EU project SOCIOTAL, resulting in a series of workshops with groups of citizens in two cities, where the issues they face and how IoT could help and improve the citizen quality of life were discussed. The drivers and barriers for IoT as well as the results of these workshops are presented in this paper, among which we highlight the main requirements for defining effective user-centric services.